2023
DOI: 10.1007/s00011-023-01723-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of COVID-19 infection in dialysis patients and protective effect of COVID-19 vaccine

Abstract: Background and objective COVID-19 infection poses a special challenge to patients with dialysis patients. The purpose of this study was to evaluate the clinical manifestations of dialysis patients with COVID-19 and the protective effect of the vaccine. Methods We included 41 studies based on big data, mainly analyzing the clinical symptoms of dialysis patients with COVID-19, the proportion of severe patients before and after vaccination, and the humoral reaction of vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 105 publications
2
5
0
Order By: Relevance
“…Previous literature has identified several demographic and clinical prognostic factors in HD with COVID-19 [18,[25][26][27][28][29]. Advanced age constitutes not only a risk factor for SARS-CoV-2 infection but also a negative prognostic factor for HD patients with COVID-19 [18]. Our study corroborates these findings, as we identified age as an independent factor for disease progression to critical illness and in-hospital mortality, aligning with previous research [25,30].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previous literature has identified several demographic and clinical prognostic factors in HD with COVID-19 [18,[25][26][27][28][29]. Advanced age constitutes not only a risk factor for SARS-CoV-2 infection but also a negative prognostic factor for HD patients with COVID-19 [18]. Our study corroborates these findings, as we identified age as an independent factor for disease progression to critical illness and in-hospital mortality, aligning with previous research [25,30].…”
Section: Discussionsupporting
confidence: 92%
“…COVID-19 infection poses a challenge to HD patients, with certain demographic and clinical manifestations observed in this unique population. Previous observations of dialysis cases with COVID-19 showed that diabetes and hypertensive nephropathy are the predominant kidney diseases, with most patients being over 50 years old [18]. Similarly, in the current study, chronic nephritis, diabetes, and hypertensive nephropathy accounted for 93.4% of the whole population with an average age exceeding 60 years.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Literature suggests that the observed high symptoms and clinical parameters among the patients are likely due to the combined effects of the viral infection and pre-existing kidney disease [10,38]. Fever and cough are common in viral infections; shortness of breath and compromised oxygen saturation result from respiratory involvement, exacerbated by compromised kidney and lung function; and fatigue may be heightened due to the interaction of both conditions are reported in COVID-19 [39,40].…”
Section: Discussionmentioning
confidence: 99%